PENGARUH KOMPENSASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN MARKETING PT. HOHO PEKANBARU - G, Rizal; Amsal, Chairul; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted with descriptive and quantitative methods that use primary data and secondary data obtained through interviews/interview and questionnaire study. Respondents were drawn were 58 people. These samples are used for the purpose of collecting the necessary data in the descriptive analysis determined accidental random sampling. Descriptive analysis of the results it can be concluded that the results of the study are the results of the overall respondents about factors at work compensation of employees of PT. HOHO Pekanbaru in the category are not good, the results are the results of the overall respondents regarding employee discipline factor PT. HOHO Pekanbaru in quite well and the results of that research respondents overall results of the performance factors of employees of PT. HOHO Pekanbaru in a category quite well. Of both the independent variables are X1 (compensation) and X2 (work stress) are the most dominant influence on the performance of employees of PT. HOHO Pekanbaru is compensation (X1), it can be seen from the t value for X1 is equal to 8,276 while the t-table is (0.05, 55) = 1.672 because t (8276)> t table (1.672) then Ho significant. Therefore, the authors advise leaders should consider the issue of compensation to be received by the employee, because of the work that employees do a compensation factor can be determined motivation and employee morale in the work so that it can have an impact on labor discipline and employee performance.Keywords: Compensation, Job Stress and Performance